Organização comunitária e desenvolvimento territorial: o contexto ribeirinho em uma ilha da Amazônia - RODRIGUES, Eliana Teles (Universidade Federal do Pará, 2011)
This is a case study about riverine communities in the Amazon estuary. It analyzes the social and spatial dynamics, as well as the community organization of the resident population in Combu Island. The spatial and territorial organization of the communities is investigated through the production and reproduction of the material and economic life, in the search of experiences which can reference other rural communities vis-à-vis the debate on regional development. Fifty-four family units were studied in four communities: Igarapé Combu, Beira do Rio, Piriquitaquara, and Furo do Benedito. For being a nature study to interdisciplinary it adopts the socioeconomic, politcs and cultural perspective having as focus the question a) How the communities of Combu island have adapted to exogenous interferences and its survival strategies; b) Which differentiation, strategy between the groups and its forms of organization and articulation; c) What generates greater community involvement. Disarticulation is an unfavorable factor in a community organization, implying fewer possibilities for communities to be a part of the society as active citizens in the development process, and in directing their own destinies. Maintaining the environment and the welfare of the population implies information and formal knowledge allied to local specific practices; the higher the degree of knowledge and local permanence, the higher is the identification, valorization, and cooperation among the riverine populations. The absence of such aspects indicates a low degree of development, or isolated practices where such aspects are hardly perceived. Alone, communities are not able to come up with dynamics to promote their welfare, but forest management developed by the riverine populations has served as a base for economic growth. Such practices may enhance açaí production the main local income source increasing families purchase power. This reinforces the argument for partnerships between institutions and communities, in order to promote environmental and social sustainability.